Association between renal tubular cell dysfunction and increased urinary zinc excretion in cancer patients - Melichar, B; Jandík, P; Malír, F; Vávrová, J; Bures, J; Mergancová, J; Voboril, Z (Scandinavian journal of clinical and laboratory investigation, 1995)
Although an increase in renal zinc excretion in cancer patients is well documented, the mechanisms involved are still disputed. As recent studies have raised the question of the role of renal tubular cell dysfunction in the elevation of urinary zinc output, we have examined urinary zinc excretion and the excretion of N-acetyl-beta-D-glucosaminidase (NAG), an indicator of tubular cell dysfunction, in 30 patients with cancer, 28 healthy controls and 20 patients with benign non-inflammatory disorders. As expected, urinary zinc excretion was significantly higher in the cancer patients compared with controls and patients with benign disorders (2.64 +/- 3.05 vs. 0.86 +/- 0.36 and 0.89 +/- 0.29 mmol mol creatinine-1, p < 0.001). NAG activity was also elevated (18.9 +/- 20.1 vs. 4.32 +/- 3.33 and 9.99 +/- 9.72 mukat mol creatinine-1, p < 0.001 and p < 0.05, respectively). A significant correlation between urine zinc and NAG was observed in all three groups (rho = 0.73, p < 0.001, rho = 0.55, p < 0.01 and rho = 0.45, p < 0.05, respectively). In conclusion, our data provide additional support for the role of renal tubular cell dysfunction in hyperzincuria in cancer. Urinary zinc measurement may represent an alternative approach to detecting renal tubular dysfunction in human pathology.
Keywords: senioři; acetylglukosaminidasa; Zinc; senioři nad 80 let; Predictive Value of Tests; Middle Aged; mužské pohlaví; prediktivní hodnota testů; Acetylglucosaminidase; Neoplasms; ledvinové kanálky; Aged, 80 and over; ženské pohlaví; Kidney Tubules; Humans; nádory; lidé středního věku; zinek; Female; Aged; lidé; Male